Women struggle for sustainability - Sarkar, Siddhartha (New Delhi : Serials Publications, 2006)
Study of the social and economic conditions of women domestic and tobacco workers in Koch Bihar, India.
Includes bibliographical references and index.
Keywords: Women struggle -- India -- Social conditions